Are there any differences in power performance and morphological characteristics of Croatian adolescent soccer players according to the team position? - Sporis, G.; Vucetic, R.; Jovanovic, M.; Milanovic, Z.; Rucevic, M.; Vuleta , D. (Collegium Antropologicum, 2011)
The aim of the study was to analyze differences in power performance and morphological characteristics of young Croatian soccer players with respect to their team positions and to establish correlations between the power performance variables. Anthropometric characteristics and jumping and sprint performances were analyzed for 45 soccer players (age 14-15; mean body height 175.4±6.61 cm; body weight 63.6±8.06 kg) acacording to their team positions (defender, midfielder, forward). Pearsons coefficient of correlation was used to determine the relationship between the power performance variables. There were no significant differences (p>0.05) in the power performance of players according to their team position. The only significant differences between players were in some of the anthropometric characteristics, such as height and weight linear relationship was determined between almost all the power performance variables. Since the players in this study were very young and their sports careers have not reached their peak performance, it is possible that their nominal team positions may change during their soccer careers.